Gambaran Kadar Kreatinin pada Penderita Hipertensi di Kecamatan Astana Anyar - Melati Sundayani Putri; Agus Sudrajat (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to describe the creatinine levels in hypertension patients in Astana Anyar District. Creatinine is an important indicator of kidney function, and increased creatinine levels are often associated with kidney dysfunction, which can be influenced by hypertension. This study used a descriptive method with a sample of 30 hypertension patients randomly selected. Creatinine levels were measured through blood analysis using an enzymatic method. The results showed that 30% of the samples had creatinine levels above normal, indicating possible kidney dysfunction. Additionally, a positive correlation was found between the severity of hypertension and increased creatinine levels. These findings highlight the importance of routine monitoring of creatinine levels in hypertension patients for early detection and management of kidney disorders. Further research is needed to understand the mechanisms underlying the relationship between hypertension and increased creatinine levels, as well as effective interventions to manage this condition.